Navigasi Menuju Pendidikan Inklusif Berkualitas melalui Program Unggulan (Studi Kasus Pondok Pesantren Walisongo Pontianak) - Hidayat, Adam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Inclusive education has become a central issue in the field of education, including within Islamic educational institutions such as pesantren. Walisongo Pesantren has demonstrated its commitment to realizing inclusive education through its outstanding programs, particularly in the fields of Arabic language and Da'wah Expeditions. This case study aims to analyze how the Arabic language and Da'wah Expedition programs at Walisongo Pesantren contribute to creating a quality and inclusive learning environment for all students. The analysis focuses on the design of the Arabic curriculum that accommodates the diverse abilities of students, the implementation of innovative and inclusive teaching methods within the Arabic program, the role of Da'wah Expeditions in facilitating social interaction and personal development for students from various backgrounds, and the efforts of the pesantren to address challenges and obstacles in achieving inclusive education. The research findings indicate that the Arabic language and Da'wah Expedition programs at Walisongo Pesantren have successfully created an inclusive and empowering learning space. The flexible Arabic curriculum, varied teaching methods, and Da'wah Expedition activities that involve all students have provided opportunities for every student to develop their potential and actively participate in learning. This study concludes that these exemplary programs can serve as models for other pesantren in their efforts to realize inclusive education. Furthermore, this research offers recommendations for the development of similar programs in the future.